2017
DOI: 10.1021/jacs.7b03116
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Chiral Selection of Aspartic Acids by Dynamic States of Brushite

Abstract: We herein show the chiral recognition and separation of aspartic acid (Asp) enantiomers by achiral brushite due to the asymmetries of their dynamical steps in its nonequilibrium states. Growing brushite has a higher adsorption affinity to d-Asp, while l-Asp is predominant on the dissolving brushite surface. Microstructural characterization reveals that chiral selection is mainly attributed to brushite [101] steps, which exhibit two different configurations during crystal growth and dissolution, respectively, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The retention times of l - and d -Asp were ~15.3 min and 20.0 min, respectively. The concentrations of l - and d -Asp in various solutions were determined from respective standard curves, and reported by using the RP-HPLC peak areas of l - and d -Asp obtained from the chiral column 28 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The retention times of l - and d -Asp were ~15.3 min and 20.0 min, respectively. The concentrations of l - and d -Asp in various solutions were determined from respective standard curves, and reported by using the RP-HPLC peak areas of l - and d -Asp obtained from the chiral column 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Enantiomers of the acidic amino-acid aspartic acid (Asp)—a particularly abundant acidic residue of biomineralization-regulating proteins—can transfer their chirality to achiral inorganic materials to form chiral architectures 2427 ; this transfer process has been proposed to play an important role in the origin of Nature’s homochiral biomolecules, where they may have assembled and organized on mineral surfaces in prebiotic conditions 28,29 . In addition, it has also been found that Asp oligomers [poly(aspartate)] and Asp-rich polymers can induce helical calcium carbonate vaterite structure 30,31 , and the chirality of helical vaterite structure is dependent on the chirality of Asp-rich polymer 31 .…”
Section: Introductionmentioning
confidence: 99%
“…At 300 K, the present force field gives deviations in the lattice parameters relative to the experimental values [27] of ∆a −0.03% ∆b −1.03% and ∆c +7.48%. As compared to the force field reported by Jiang et al (at 300 K: ∆a 3.89% ∆b +1.96% and ∆c +1.32%), this force field performs more accurately in the a and b directions, but worse in c [20]. We also modified the parameters of [24] to produce a force field (C2) which more closely matched the experimental lattice parameters (See Table S1 in the Supplementary Information for force field parameters).…”
Section: Methodsmentioning
confidence: 84%
“…Although there have been studies of the brushite-water interface, to date there has been no precise determination of the water ordering. Jiang et al [20] studied the adsorption of aspartic acid on brushite and as a part of their study attempted to reproduce the SXRD spectrum from Arsic et al [16]. The force field employed was based upon existing interatomic potentials (OPLS-AA [21], TIP3P water model [22]) with modifications for brushite based on Hauptmann's model [23] with partial charges from density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, l -(+)-Tar does and inhibits mineral crystal growth. 18 , 39 The theory behind this process is described in Figure 1…”
Section: Introductionmentioning
confidence: 99%